Impact of biochar on the fungal decay resistance of hemp-polylactic acid composites against wood basidiomycetes - Zouari, Mariem; Mikuljan, Marica; Schwarzkopf, Matthew (Frontiers in Materials, 2023)
The effect of fungal decay on the physiological and morphological properties of polylactic acid (PLA) composites reinforced with hemp fibers and incremental loading of biochar (BC) (0, 5, 10, and 20 wt %) was evaluated. Two species of wood fungi: Trametes Versicolor and Fomitopsis Betulina were incubated with the composites for five months. Weight loss, color change, microscopic observations, and contact angle were evaluated during and after the five-month incubation period. We found that the total weight loss decreased with increasing BC content up to 10 wt%. The color stability of composites loaded with 10 wt% of BC was better than those without BC. Micrographs revealed that white and brown rots invaded the surface of the composites at the beginning of the incubation period and then accessed the interior of the materials. Micro-cracks occurred in composites containing hemp fibers which enabled the fungi to invade the internal structure of the composites. At the same time, fungi grew on the surface of samples without hemp fibers except for PLA with 20% BC content which had a porous surface that allowed fungi to access the interior. The hydrophobicity of all samples increased during the first three months of the incubation and then decreased again by the end of the incubation as the surface of the composites started to be damaged.